Statistical physics of fracture, breakdown, and earthquake : effects of disorder and heterogeneity /: effects of disorder and heterogeneity. (2015) - Biswas, Soumyajyoti; Ray, Purusattam; Chakrabarti, B. K (Bikas K.), 1952-
No abstract available